2019
DOI: 10.2215/cjn.10350818
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Organic Anion Transporter-Mediated Tubular Secretion during Postnatal Human Kidney Development and Maturation

Abstract: Background and objectives The neonatal and juvenile human kidney can be exposed to a variety of potentially toxic drugs (e.g., nonsteroidal anti-inflammatory drugs, antibiotics, antivirals, diuretics), many of which are substrates of the kidney organic anion transporters, OAT1 (SLC22A6, originally NKT) and OAT3 (SLC22A8). Despite the immense concern about the consequences of drug toxicity in this vulnerable population, the developmental regulation of OATs in the immature postnatal kidney is poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Due to the lack of information regarding SLC22 fruit fly orthologs, we attempted to characterize and classify them utilizing multiple sequence alignments and RNAi knockdowns. Because there are minimal developmental phenotypes (apart from Octn2) for single SLC22 knockouts in mice despite developmentally interesting and highly dynamic expression patterns, developmental phenotypes observed in Drosophila could help further our understanding of how SLC22 contributes to development in other organisms as well [19,[28][29][30][31]. Prior to our analysis, only three (BalaT, CarT and SLC22A) out of the 25 fruit fly SLC22 orthologs were functionally investigated beyond global tissue expression screens and homology studies [5,10,15,43,51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of information regarding SLC22 fruit fly orthologs, we attempted to characterize and classify them utilizing multiple sequence alignments and RNAi knockdowns. Because there are minimal developmental phenotypes (apart from Octn2) for single SLC22 knockouts in mice despite developmentally interesting and highly dynamic expression patterns, developmental phenotypes observed in Drosophila could help further our understanding of how SLC22 contributes to development in other organisms as well [19,[28][29][30][31]. Prior to our analysis, only three (BalaT, CarT and SLC22A) out of the 25 fruit fly SLC22 orthologs were functionally investigated beyond global tissue expression screens and homology studies [5,10,15,43,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Without carnitine supplementation, Octn2 KO mice develop dilated cardiomyopathy, fatty livers and steatosis of other organs, and expire in 3-4 weeks [24]. Although Oat KO's (including Slc22a12) and Oct KO's have abnormal levels of metabolites and signaling molecules, with only one clear developmental phenotype observed thus far in mice, determining the functional importance of these genes in Drosophila could provide insight for orthologous developmental roles in mice and humans given their interesting developmental expression patterns [19,[28][29][30][31]. As an initial developmental screen, we created ubiquitous RNAi knockdowns driven by a ubiquitous da-GAL4 driver of 14 of the putative SLC22 orthologs and observed their development.…”
Section: Introductionmentioning
confidence: 99%
“…During covariate exploration, maturation functions for glomerular filtration rate, and renal plasma blood flow were evaluated to describe the change of CL with age. 40,43 Compared to the final model, a slightly worse model fit (OFV = 3.0) was obtained from the model with fixed values of maturation function parameters for glomerular filtration rate, 43 and a substantially worse model fit (OFV = 22.9) was obtained from the model with fixed values of maturation function parameters for renal plasma blood flow. Importantly, the rise of OFV did not reach the statistical significance threshold when maturation values were fixed at prior estimates of glomerular filtration rate maturation; therefore, we cannot definitely rule out that HCTZ maturation ultimately develops similarly to glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 87%
“…One human study examining para‐aminohippurate excretion in the kidney, which displays 90% renal excretion and is believed to be primarily mediated by OAT1 and OAT3, concluded that the maturation of OAT transporters increased markedly in the postnatal period and reached half of adult values at 2 years of age 40 . In the pediatric model characterized in this report, maturation parameters in our equations suggested that HCTZ CL/F reached half of adult CL/F values by 39.3 weeks PMA, which is earlier than the para‐aminohippurate study previously suggested in the murine and human models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation